Clinical features of ankylosing spondylitis in patients with secondary AA amyloidosis - D. G. Rumyantseva; E. M. Agafonova; S. O. Krasnenko; A. S. Starkova; M. M. Urumova; Sh. Erdes (Современная ревматология, 2020)
Renal AA amyloidosis is the most severe type of renal pathology in patients with ankylosing spondylitis (AS). The characteristic symptoms of AA amyloidosis in rheumatic diseases do not often occur for years, making it difficult to diagnose it early and to start adequate therapy.Objective: to identify the clinical features of AS complicated by secondary AA amyloidosis.Patients and methods. The investigation enrolled 9 patients with AS (according to the 1984 modified New York criteria) and histologically confirmed secondary AA amyloidosis (Group 1). A comparison group included 216 AS patients without amyloidosis (Group 2).Results and discussion. In Group 1 patients, the age at the onset of AS was significantly less and the disease duration was 4 times longer than those in Group 2. All the patients with AA amyloidosis had enthesitis and arthritis, including those of the hip joints. The scores of the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and the Ankylosing Spondylitis Disease Activity Score with C-reactive protein (ASDAS-CRP), and the acute phase inflammation index CRP were higher in Group 1 than in Group 2.Conclusion. The clinical feature of AS complicated by secondary AA-amyloidosis is the long duration of the disease and the high frequency of juvenile onset, non-axial manifestations (arthritis, coxitis and enteritis), as well as the high activity of systemic inflammation.